PERENCANAAN LABA DAN PENJUALAN DENGAN ANALISIS COST-VOLUME-PROFIT - Fabiola Damaiyanti Haryati (Universitas Pendidikan Nasional, 2013)
The purpose of this study was to: (1) to determine the position of the state sales breakevenpoint (BEP), (2) to determine the volume of sales with a profit target, (3) to determinethe volume of sales with a profit target of interest and the cost of change fixed, (4) todetermine the safety limit sales declines tolerated the presence of the target label set (Marginof Safety), (5) To determine the strategic steps that must be performed in the presence ofprofit planning. Analytical techniques used in the study is cost-volume-profit (CVP) analysisis an analysis of the relationship between cost, volume, and profits produced by the companyas well as sensitivity analysis in achieving sales and profit targets.The conclusion is (1) Sales in breakeven position (break even) at Dalem PuriDenpasar Hotel is at Rp.3.537.538.969, (2) the volume of sales that must be done to achievethe profit target, which is assumed if the desired profit rose 20% in the amount ofRp.968.122.558 then the company should conduct sales of Rp.4.998.997.222 whereas if theassumed profit rose 30% in the amount of Rp.1.048.799.438 then the company shouldconduct sales of Rp.5.120.785.409, (3) the volume of sales that must be done to achieve atarget profit if fixed costs are assumed to increase with earnings up 10% up 20% then salesshould be done by the company amounted to Rp.5.352.751.119. Whereas if the earnings rise30%, then the sale of the company is to be done by Rp.5.474.539.306. As for the assumptionof fixed costs rose 20% with profit up 20%, then sales should be done by the companyamounted to Rp.5.706.505.016. Whereas if the earnings rise 30%, then the sale of thecompany is to be done by Rp.5.828.293.203, (4) safety limit sales declines tolerated thepresence of the target label set (Margin of Safety) when assuming earnings rose 20%, theMOS companies amounted Rp.1.461.458.253 whereas if assuming profit rose 30%, thecompany is at Rp.1.538.246.440 MOS.Keywords: CVP Analysis, profit targets, sensitivity.